Intergenerational Transmission of the Behavioral Consequences of Early Experience in Prairie Voles - Stone, Anita Iyengar (2010)
We examined intergenerational and epigenetic effects of early handling manipulations on the social behavior of the prairie vole (Microtus ochrogaster), a monogamous rodent. Laboratory-born parents and their newborn pups were assigned to either a MAN0 “zero handling” manipulation (transfer with a cup during weekly cage changes) or a MAN1 “gloved handling” manipulation (transfer with a gloved hand). Previous studies from our laboratory (Bales et al. 2007) showed that MAN0 juvenile males that received this manipulation as pups are less alloparental and that MAN0 adult females that received this manipulation as pups display impaired pair-bonding. In the present study, when MAN0 and MAN1 pups reached adulthood, they were mated in three combinations (MAN1 female × MAN1 male; MAN0 female × MAN1 male; MAN1 female and MAN0 male). Once the pairs produced offspring, we examined their parental behavior towards their own pups. The offspring of these pairings (F2 generation) also were tested as juveniles for alloparental behavior. MAN1 females paired with a MAN0 male displayed higher levels of parenting behaviors. In the F2 generation, juvenile offspring with a MAN0 parent were less alloparental than were offspring from other pairs. These results suggest that early experiences can be transmitted intergenerationally.